ANALYSIS OF CIPP EVALUATION MODEL ON RELIGIOUS PROGRAMS IN SCHOOLS: SYSTEMATIC LITERATURE REVIEW - Alsya'bani, Ibnu Syakur; Madjid, Abd.; Shodiq, Sadam Fajar (JURNAL EDUSCIENCE, 2025)
Purpose – This study aims to analyze the application of the CIPP (Context, Input, Process, Product) evaluation model in school religious programs, focusing on identifying factors that affect the effectiveness and utilization of evaluation results for program development. The background of this research is the importance of comprehensive evaluation in religious education programs to ensure the achievement of goals that are by the vision and needs of students.Methodology—This study uses the Systematic Literature Review (SLR) method to review and analyze 34 articles published between 2015 and 2024 on applying the CIPP model in religious programs at various levels of education. The analysis is carried out on a thematic basis to identify the main themes that emerge from the articles.Findings – Key findings suggest that the CIPP model provides a holistic evaluation of religious programs, covering aspects of context, inputs, processes, and products that allow for identifying strengths and weaknesses in each stage of program implementation. Factors that affect the program's effectiveness include the quality of human resources, facilities, learning methods, and the involvement of stakeholders such as teachers and parents. The results of this evaluation are used to improve the program's quality, for example, through teacher training, improvement of teaching methods, and the use of technology in learning.Significance—This study is significant because it provides insight for education managers, especially in schools that implement religious programs, to implement CIPP model-based evaluations to increase the effectiveness and sustainability of religious programs in schools.